Energy drinks alter the surface morphology and roughness of composites, fissure sealants and titanium An in vitro study - Kolarovszki Béla (HELIYON, 2022)
Objectives The influence of energy drinks on dental materials are relatively under addressed. Our aim was to investigate the effect of energy drinks on dental materials used intraorally in young individuals. Commonly used preventive, restorative, and orthodontic materials were tested in vitro. Methods The effect of two commercially available energy drinks (HELL, BURN) was investigated on different dental materials: machined, anodized Titanium (grade 5: Ti6Al4V) and composites (Grandio Seal, VOCO; Filtek Z250, 3M ESPE; Estelite SQ, TOKUYAMA). The roughness (Ra) and morphological changes were examined by atomic force microscopy (AFM) and scanning electron microscopy (SEM). Results AFM and SEM revealed significant differences in the Ra and morphology of the samples. AFM results for the machined and anodized titanium samples showed that the two energy drinks modified the surface roughness differently; BURN changed the roughness of machined samples significantly, while anodized discs were not altered significantly by the two energy drinks. In case of composite samples there was no significant difference for the Estelite SQ, relative low differences for the Filtek Z250 and significant changes in the morphology and surface roughness of Grandio Seal. Significance On all tested materials, changes in the surface roughness and morphology were more or less detected, proving energy drinks do in fact have a harmful effect. It can be concluded that material erosion depends on the material composition and particle arrangement. Where the surface is characterized by a regular, uniform particle arrangement, energy drinks are less able to influence the roughness, while for samples where the surface is rich in aggregates, the material erodes the surface much more easily.